A spectroelectrochemical study of the inhibition of the electrode process on copper by 2-mercaptobenzothiazole in ethanolic solutions - Marconato, J. C.; Bulhoes, L. O.; Temperini, M. L. (Elsevier B.V., 1998)
The effect of 2-mercaptobenzothiazole (MBT) on the corrosion of copper in ethanol-water mixture with 0.01 mol dm(-3) HClO4 was investigated by linear sweep voltammetry and surface enhanced Raman scattering spectroscopy. The linear sweep voltammetry for the copper electrode in the presence of MBT shows one anodic process associated with the oxidation of MBT, which leads to the formation of a film on the electrode. This film inhibits the anodic copper dissolution and cathodic hydrogen evolution reaction. SERS studies indicated that MBT oxidizes and forms polymeric complexes involving copper ions and the ionized form of thiol. (C) 1997 Elsevier B.V. Ltd.
Keywords: 2-mercaptobenzothiazole; SERS; ethanol; copper corrosion